Bridging the experience and perception gap through 360-degree brand campaign: a case of Banglalink Fastest 4G - Sakib, MD. Nazmus (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.